Handbook of research on discourse behavior and digital communication [ language structures and social interaction - Taiwo, Olurotimi Adebowale (Gale virtual reference library, 2010)
"This book provides a variety of chapters on discourse behavior in digital communication, including computer-mediated communication as well as aspects of behavior typically associated with online discourse like cyberbullying" -- Provided by publisher